PENGARUH MODEL PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATERI SISTEM KOORDINASI KELAS XI SMAN 7 PEKANBARU - Yolanda, Mercy; Mahadi, Imam; Yustina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyse the creative thinking abilities of students influenced by the Project-Based Learning (PjBL) model in the coordination system material for Grade XI at SMAN 7 Pekanbaru. The study was conducted at SMAN 7 Pekanbaru, Senapelan District, Pekanbaru City, in May 2025 during the 2024/2025 academic year. This research is a quasi-experiment with a pretest–posttest control group design. The research population included all 142 Grade XI students at SMAN 7 Pekanbaru. Samples were selected randomly, with Grade XI4 as the experimental class and Grade XI8 as the control class. The research parameter was students' creative thinking skills, which were measured through four indicators, namely fluent thinking, flexible thinking, original thinking, and detailed thinking. Data collection techniques used multiple-choice test questions, observation sheets, and product assessment sheets. Data analysis techniques included instrument feasibility testing, prerequisite testing, and independent t-testing. The results showed a Sig value of 0.01 < 0.05 and a t-count of 7.580 > t-table = 1.667, so H₀ was rejected and H₁ was accepted. Based on the results of the study, it can be concluded that using the Project Based Learning model can improve the creative thinking abilities of grade XI students at SMAN 7 Pekanbaru.